Mother Tongue in Educating Modern Language Personality (Linguostylistic Studies, 2018)
The study seeks to prove that the issue of language stability and its sources are the key concerns for sociolinguistics and acquires special importance when the processes of language assimilation threaten a national language. The mastery and practical use of the mother tongue is a psychological problem. Since the language itself, via the memory of the previous generations, has developed the national image of the world, owing to those generations, to return this image both to modern national memory and to the source of the state language is a task, even an obligation of the nation, which is not limited to the family and school only. Formation of spirituality is a shared responsibility of the society on the whole and involves educating people in this domain. This education depends on many factors: the desire or unwillingness of the people, their worldview or their opting for forgetting rather than preserving the native gene pool and its purity, sedentariness of the nation, expression of public and personal will. All these issues are actualized by psycholinguistics. Language develops and improves thinking and spiritual life not only of a child but also of an adult. Caring for the harmonious development of humankind, the unity and functional sufficiency of the national language can ensure the harmony of universal human relations
Keywords: ethnolinguistics; sociolinguistics; social status of speakers; thought and dictum; language norms